Developing a green-oriented curriculum for vocational high schools in housing and construction: addressing skill gaps through tyler’s theory - Ahmed Gaber Abedelhamid; Ivan hanafi Hanafi; M. Agpin Ramadan Ramadan (Universitas Sarjanawiyata Tamansiswa, 2025)
This study develops a green-oriented curriculum for vocational high schools (SMK) in Jakarta, specifically in the housing and construction field, in response to global trends in sustainable building. The research was conducted using a qualitative descriptive approach, combining curriculum analysis with expert interviews to identify gaps between existing competencies and the skills demanded in green construction projects. Tyler’s curriculum development model served as the guiding framework to translate industry needs into learning objectives, outcomes, and structured subjects. Findings show that while the current curriculum provides a strong foundation in conventional hard and soft skills, it lacks coverage in minor hard green skills and general green knowledge. To address these gaps, the study proposes the integration of two new main hard skill subjects, six minor hard green skill subjects, five green soft skill subjects, and four general green knowledge subjects. This increases the curriculum from 84 to 101 subjects, ensuring graduates are better prepared to meet international standards for green building and contribute to climate change mitigation. The results suggest that curriculum modification does not require a complete restructuring but rather strategic additions that align vocational education with labor market demands in the green economy. This study offers a pioneering framework for bridging vocational education with global sustainability goals, with implications for future implementation, pilot testing, and collaboration with industry stakeholders.